Differential circulating cytokine profiles in acute coronary syndrome versus stable coronary artery disease - Maaniitty, Eveliina; Jalkanen, Juho; Sinisilta, Sami; Gunn, Jarmo; Vasankari, Tuija; Biancari, Fausto; Jalkanen, Sirpa; Airaksinen, K. E. Juhani; Hollmen, Maija; Kiviniemi, Tuomas (Springer Nature, 2025)
Chronic inflammation plays a crucial role in coronary artery disease (CAD), but differences in specific cytokine profiles between acute coronary syndrome (ACS) and stable CAD remain unknown. We investigated cytokine differences between these two manifestations of CAD. The study included 308 patients with angiographically detected, hemodynamically significant CAD: 150 patients undergone angiography for ACS, 158 patients undergone angiography for stable CAD. To assess dynamic changes, 116 patients had index angiogram at least 3 months earlier. We measured the serum concentrations of 48 circulating cytokines. The ACS group had decreased interleukin (IL) 4 (p = 0.005), and increased IL-8 (p = 0.008), hepatocyte growth factor (HGF) (p < 0.001) and macrophage colony-stimulating factor (M-CSF) (p = 0.002) levels compared with the stable CAD group. Multivariable logistic regression revealed increased levels of HGF (OR 18.050 [95% CI 4.372-74.517], p < 0.001), M-CSF (OR 2.257 [1.375-3.705], p = 0.001) and IL-6 (OR 1.586 [1.131-2.224], p = 0.007), independently associated with ACS. In the post-angiography group, only diminished platelet-derived growth factor-BB levels in ACS-manifested patients were observed (OR 0.478, [0.279-0.818], p = 0.007). Cytokine profiles differ between ACS and stable CAD. Such differences seem to be mainly reversible within 3 months after ACS. Thus, targeting one or two cytokines only might not offer one-size fits all-therapeutic approach for CAD-associated inflammation.Trial registration: NCT03444259.